The use, and usefulness, of spatial conservation prioritizations - Sinclair, SP; Milner-Gulland, EJ; Smith, RJ; McIntosh, EJ; Possingham, HP; Vercammen, A; Knight, AT (Wiley, 2018)
Spatial conservation prioritization is used globally to guide decision making with the aim of delivering the best conservation gain per unit investment. However, despite many publications on the topic, the extent to which this approach is used by decision makers has been unclear. To investigate the degree to which prioritization has been adopted by practitioners to guide conservation implementation we conducted an online survey, collecting data on the approaches used to develop prioritizations and the reported extent of translation to on‐the‐ground action. Using a cluster analysis, we identified two categories of prioritizations, those developed to advance the field (42% of responses) and those intended for implementation (58% of responses). Respondents reported 74% of the prioritizations intended for implementation had translated to on‐the‐ground action. Additionally, we identified strong collaboration between academics and practitioners in prioritization development, suggesting a bridging of the theory‐practice gap. We recommend continued collaboration and research into the effectiveness of prioritizations in delivering conservation impacts.